Analisis Strategi Penerjemahan Ekspresi Idiomatik dan Kesepadanan Makna dalam Film Set It Up - Ida Husniati; Misyi Gusthini (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study is motivated by the importance of accurately translating idiomatic expressions in audiovisual media in order to maintain meaning equivalence between the source language and the target language. Idiomatic expressions, as forms of non-literal expressions, often create difficulties in the translation process. This study aims to analyze the translation strategies used in translating idiomatic expressions in the film Set It Up and to evaluate the level of meaning equivalence in the translated version. The research employed a descriptive qualitative method with a content analysis approach, which included the identification, classification, and interpretation of data in the form of idiomatic expressions found in the film dialogues and their Indonesian translations. The results indicate that various translation strategies were applied, such as the use of equivalent meanings, paraphrasing, and omission in certain contexts. The level of meaning equivalence varied depending on the selected strategies and their contextual use. This study is expected to provide insight into the complexity of translating idiomatic expressions in audiovisual media and its contribution to audience comprehension.